Role of Growth Center: A Rural Development Perspective - Biplob Kanti Mondal; Kausik Das (Journal of Bangladesh Institute of Planners, 2010)
This paper incorporated the upshot of growth centre for economic & social development of rural Bangladesh. An attempt has been made to expose the changes in social life as well as in physical development of the area after built up the Growth centre. In recent years the purchasing intensity of various sector’s (agriculture, fisheries etc.) input increased very fast. Thus, the more increase in the numbers of buyers in these markets, more will be the trade volume and turn over which perpetuate local development. But these rural markets are beset with many problems which are mostly associated with infrastructure. Growth centers with better infrastructure facilities are likely to play a wider role in the rural economy & development. It has been seen that provision of infrastructure in rural markets actually paves the way for employment generation and contributes to increasing number of traders and market turnover. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 129-141